2023
DOI: 10.1136/bmjopen-2022-070694
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric oncology nursing education and training programmes: a scoping review protocol

Maureen Daisy Majamanda,
Felix Chisoni,
Apatsa Selemani
et al.

Abstract: IntroductionThe care of children with cancer is a highly specialised field which requires well-educated, trained and dedicated nurses to provide high-quality care. In low/middle-income countries, the survival rate of children with cancer is low as compared with that of high-income countries due to the limited number of specialised oncology healthcare professionals, especially nurses. To address this problem, a number of paediatric oncology education and training programmes have been developed for nurses. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…7 A study conducted in 2022 in the field of oncology nursing, which showed a significant 40% improvement in compliance with legal regulations after implementing similar educational initiatives. 8 Applying this achievement to the field of paediatric nursing has the potential to greatly improve patient outcomes and adherence to legal requirements, hence decreasing the occurrence of disputes and ethical grievances. 9 It is especially important because a recent audit by the National Paediatric Hospital Alliance (2023) revealed that only 50% of incidents related to ethical concerns were addressed per the recommended criteria for best practices.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study conducted in 2022 in the field of oncology nursing, which showed a significant 40% improvement in compliance with legal regulations after implementing similar educational initiatives. 8 Applying this achievement to the field of paediatric nursing has the potential to greatly improve patient outcomes and adherence to legal requirements, hence decreasing the occurrence of disputes and ethical grievances. 9 It is especially important because a recent audit by the National Paediatric Hospital Alliance (2023) revealed that only 50% of incidents related to ethical concerns were addressed per the recommended criteria for best practices.…”
Section: Introductionmentioning
confidence: 99%